Anatomy of the cerebellopontine angle - Grunwald, I; Papanagiotou, P; Nabhan, A; Politi, M; Reith, W (2006)
The cerebellopontine angle (CPA) is an anatomically complex region of the brain. In this article we describe the anatomy of the CPA cisterns, of the internal auditory canal, the topography of the cerebellum and brainstem, and the neurovascular structures of this area. © Springer Medizin Verlag 2006.